A Comparison of Four Caries Risk Assessment Methods - Featherstone, John D. B.; Crystal, Yasmi O.; Alston, Pamela; Chaffee, Benjamin W.; Doméjean, Sophie; Rechmann, Peter; Zhan, Ling; Ramos-Gomez, Francisco (Frontiers in Oral Health, 2021)
Introduction: Caries risk assessment (CRA) is essential as the basis for successful management of dental caries. Of the many published CRA tools, four well-known ones are CAMBRA, Cariogram, American Dental Association (ADA), and American Academy of Pediatric Dentistry (AAPD) CRAs. The predictive accuracy of CAMBRA and Cariogram CRA tools have been examined in clinical outcomes studies in thousands of patients and the tools are widely used all over the world. The purpose of the present paper is three-fold, namely (1) to briefly review, compare and contrast these four CRA methods, (2) to provide a concise method for CRA introducing a quantitative component to the CAMBRA forms (CAMBRA 123), and (3) to guide the choice of CRA methods that will support caries management decisions. Comparison of Caries Risk Assessment Methods: In the present evaluation, the above-mentioned four CRA methods for ages 0–6 years and 6 years-adult were compared using 26 hypothetical patients (13 per age group). Comparison results show that Cariogram and CAMBRA categorized patients into identical risk categories. Each of the ADA and AAPD tools gave different results than CAMBRA and Cariogram in several comparison examples. CAMBRA 123 gave the same caries risk level results as the Cariogram and the CAMBRA methods for all hypothetical patients for both age groups. Conclusions: Both the Cariogram and the CAMBRA CRA methods are equally useful for identifying the future risk of dental caries. CAMBRA 123 shows promise as an easy-to-use quantitative method for CRA in clinical practice. The health care providers will be the ones to decide which CRA method will allow them to establish individualized, successful caries management therapies and how to combine these for the best care of their patients.